GOOD GOVERNANCE IN NIGERIA: WHAT ROLE FOR THE MEDIA - Dunu, Ifeoma (European Scientific Journal, ESJ, 2013)
The media over the years have been globally acknowledged as the watch dog of the society and their information/monitoring roles considered a sine qua non for democracy and good governance. Nigeria like most other democratic countries entrenched the principles of Good Governance as possible criteria for democratic governance in her 1999 constitution. However, despite this constitutional provision, as well as the enormous financial resources, and huge potentials of the country, good governance continues to be elusive to Nigeria. This paper argues that media’s potential to contribute to Good Governance depends on the extent the media reflect and enforce the principles of good governance as an institution. The paper also identifies why and how the media are critical sectors in shaping governance while highlighting some of the principal opportunities and challenges to engaging with the sector. This work also provides a critical discourse of the concept of good governance. The paper concludes that for the media to contribute effectively in enthroning good governance, they must as a matter of responsibility apply the basic principles of patriotism, accountability, transparency and objectivity in the discharge of their duties and uphold the sanctity of truth and fairness at all times.